TEMPERATURE AND DENSITY OF THE TYRRHENIAN LITHOSPHERE AND SLAB AND NEW INTERPRETATION OF GRAVITY FIELD IN THE TYRRHENIAN BASIN - Cella F.; de Lorenzo S.; Loddo M.; Mongelli F.; Zito G.; Fedi M.; Rapolla A. (My University, 2006)
The gravity anomaly field of the Tyrrhenian basin and surrounding regions reflects the complex series of geodynamic events active in this area since the Oligocene-Miocene. They can resume in lithospheric thinning and asthenospheric rising beneath the Tyrrhenian Basin, coexisting with the roll-back subduction of the African plate margin westward sinking beneath the Calabrian Arc. The geographic closeness between these processes implies an intense perturbation of the mantle thermal regime and an interference at regional scale between the related gravity effects. A model of the litho-asthenospheric structure of this region is suggested, showing a reasonable agreement with both the evidences in terms of regional gravity anomaly pattern and the results concerning thermal state and petro-physical features of the mantle. The first phase of this study consisted of the computation of the isotherms in the crust-mantle system beneath the Tyrrhenian Basin and, afterwards, of the density distribution within the partially melted upwelling asthenosphere. The second phase consisted of a temperature/density modelling of the slab subducting beneath the Calabrian Arc. Finally, a 21/2 interpretation of gravity data was carried out by including as constraints the results previously obtained. Thus, the final result depicts a model matching both gravity, thermal and petrographic data. They provide (a) a better definition of the thermal regime of the passive mantle rise beneath the Tyrrhenian basin by means of the estimation of the moderate asthenospheric heating and (b) a model of lithospheric slab subducting with rates that could be smaller than generally suggested in previous works. © 2005 Elsevier B.V. All rights reserved.
Keywords: ASTHENOSPHERE; CENTRAL MEDITERRANEAN; DENSITY MODEL; GRAVITY ANOMALIES; HEAT FLOW; LITHOSPHERE; SUBDUCTION; THERMAL MODEL; TYRRHENIAN BASIN; Miocene; Oligocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен